Real-world efficacy of MiniMed™780G recommended settings (glycemic target 100 mg/dL, active insulin time 2 hours) in youth and young adults with type 1 diabetes - Bassi, Marta; Spacco, Giordano; Pezzotta, Federico; Di Jorgi, Margherita; Siri, Giulia; Pintabona, Andrea; Calevo, Maria Grazia; Minuto, Nicola; Maghnie, Mohamad (Frontiers in Endocrinology, 2025)
Background and aimsDespite growing evidence supporting the efficacy and safety of the MiniMed™ 780G recommended settings (Glucose Target 100 mg/dL and Active Insulin Time 2 hours), their adoption in routine practice remains limited, mainly due to concerns about hypoglycemia. This study aimed to evaluate the impact of switching to these settings in pediatric and young patients with type 1 diabetes (T1D).MethodsWe conducted a retrospective longitudinal analysis in children and young adults using MiniMed™780G system at our center. Patients who switched from their initial settings to a glucose target of 100 mg/dL and an active insulin time of 2 hours for clinical indications were included. Data were retrospectively collected 3 months after switch. Glycemic metrics were compared over the 14 days before the switch (T0) and at 1 month (T1), and 3 months (T3).ResultsNinety-one patients with a mean age of 17.89y were included, 81.3% of whom already had a glucose target of 100 mg/dL at baseline. Therefore, in most cases the primary change was reducing AIT from 3 to 2 hours. After switching to the recommended settings, Time in Range (TIR) significantly increased (p<0.001) at T1 (71.9% vs 74.8%) and T3 (71.9% vs 75.0%). Time in target range (TITR) similarly improved from 47.2% at T0 to 51.4% at T1 and 50.9% at T3 (p<0.001) without any significant increase in time below range (TBR). The proportion of patients meeting all ADA-recommended glycemic targets rose from 29.5% at baseline to 40% at T3. Following the switch, the contribution of automatic correction boluses to the total insulin dose increased, while overall daily insulin requirements remained stable.ConclusionsSwitching to the recommended MiniMed™780G settings, driven primarily by AIT reduction in most patients, was safe and effective, improving glycemic control without increasing hypoglycemia. These findings support broader use of these settings in pediatric and young adult patient with type 1 diabetes.